Prolonged Reactive Oxygen Species Generation and Nuclear Factor-κB Activation after a High-Fat, High-Carbohydrate Meal in the Obese - Patel, Chinmay; Ghanim, Husam; Ravishankar, Shreyas; Sia, Chang Ling; Viswanathan, Prabhakar; Mohanty, Priya; Dandona, Paresh (The journal of clinical endocrinology and metabolism, 2007)
Background: Because obesity is associated with chronic oxidative and inflammatory stress, and high-fat, high-carbohydrate meals induce significant oxidative and inflammatory stress in normal subjects, we have now hypothesized that the intake of a high-fat, high-carbohydrate meal would result in a greater and more prolonged oxidative and inflammatory stress in the obese than in normal subjects. Methods: Ten normal-weight and eight obese subjects were given a high-fat, high-carbohydrate meal after an overnight fast. Blood samples were collected at baseline and hourly following the meal for 3 h. Results: Reactive oxygen species generation by mononuclear cells increased significantly by 2 h in both groups but continued to increase significantly at 3 h in the obese subjects, whereas in normal subjects it returned to baseline. Levels of p47phox increased significantly (by 81 ± 26%) at 3 h in obese individuals (P < 0.05), whereas there was no significant change in p47phox in normal subjects. Nuclear factor-κB DNA binding in mononuclear cells increased significantly (by 48 ± 58%, P < 0.036) at 2 h but not at 3 h in normal subjects, whereas in the obese, nuclear factor-κB increased significantly at both 2 and 3 h (by 36 ± 57 and 42 ± 63%, respectively, P < 0.004). Matrix metalloproteinase-9 concentrations were significantly higher in the obese at baseline (580 ± 103.9 vs. 373 ± 30.03 ng/ml, P < 0.05) and increased to significantly greater concentrations after the meal than in the lean subjects. Conclusions: High-fat, high-carbohydrate meals induced a significantly more prolonged and greater oxidative and inflammatory stress in the obese. This may contribute to the increased atherogenic risk in obesity.